Student Clubs at Universities: A Content Analysis on Diversity - Ömür Hakan KUZU (Anı Publishing, 2021)
Student clubs at universities are quite significant in acquiring many skills and competencies, especially personal, cognitive, and social development, to support students' professional and academic achievements. That being the case, this paper, a descriptive case study, aims to unveil how student clubs in Turkish state universities are diversified according to their fields of operation and university types. As of January-February 2020, 207 state and foundation universities exist in Turkey, and 11.106 student clubs information on 175 websites of these universities was attained for this research. Student clubs in the study were analysed in terms of the access information of the clubs and the number of university students. In contrast, club names were coded using the content analysis method. As a result of the analyses, it was observed that these clubs are classified under three themes, eight categories, and nineteen codes. At the end of the study, it was concluded that access to information of student clubs at Turkish universities and their visibility levels on universities' websites and other social media are rather insufficient, and some suggestions were therefore made.